Development and characterization of ZnO piezoelectric thin films on polymeric substrates for tissue repair. Issue 10 (30th May 2019) - Costa, José; Peixoto, Tânia; Ferreira, Armando; Vaz, Filipe; Lopes, Maria A.
Abstract: Currently available scaffolds for tissue repair have shown very limited success, so many efforts have being put in the development of novel functional materials capable of regulating cell behavior and enhance the tissue healing rate. Piezoelectric materials, as zinc oxide (ZnO), can be a very interesting solution for scaffold development, as they can deliver electrical signals to cells upon mechanical solicitation, allowing the development of suitable microenvironments for tissue repair. This way, it is reported the deposition of ZnO thin films on a polymer by direct current magnetron sputtering, under different conditions, in order to obtain a piezoelectric ZnO thin film with potential for tissue repair applications. The obtained ZnO thin films were characterized in terms of morphology, crystallography, electrical conductivity, transmittance, piezoelectricity, and adhesion quality. The deposition process resulted in uniform films, with a very good adhesion to the substrate. The different deposition conditions influenced the evolution of the crystalline domains and preferential growths and consequently, the electrical properties of the films. One of the conditions resulted in a thin film with a high piezoelectric coefficient and a conductor behavior, being considered the most promising to act as a bioactive coating.